North American Borders in Comparative Perspective during COVID Times - Guadalupe Correa-Cabrera; Victor Konrad (Norteamérica)
After the partial closure of the Canada-U.S. and Mexico-U.S. borders due to the COVID-19 pandemic in 2020,  and considering a new vision of border management that has been evolving since 1994, the face of North American borders is changing today. The future of the Canada-U.S. border will essentially differ from that of the Mexico-U.S. border. The first one might become more tenuous, while the border that divides Mexico and the United States will be probably fortified. Such a divergence is directly connected to the structural inequalities that characterize this region magnified by the pandemic. The present article examines North American borders in comparative perspective during COVID times. This comparative exercise focuses on four main thematic areas: trade, human mobility/migration, security and public health.